ANALISIS PEMASARAN SECARA ONLINE YANG BERDAMPAK PADA PENJUALAN FROZEN FOOD INDAH DI PASAR LEMBANG CILEDUG - Ernawati, Indah; Syah, Arman (Journal of Research and Publication Innovation, 2024)
Frozen Food Indah Store in Lembang Ciledug Market is a Frozen Food shophouse that does business in the food sector, located in the Lembang Ciledug Market Area. Frozen Food Indah in Lembang Ciledug Market wants to be one of the stores that increases food consumption in Indonesia which makes Frozen Food functional food, to be a bridge from livestock and plantations to consumers (consumers). It is hoped that the mission of Frozen Food to get closer to the residential environment of the community can be an alternative as a staple food to buy quality food. Research Objectives Based on the focus of the research above, the objectives of this study are as follows: To find out the marketing strategy by Frozen Food Indah in Lembang Ciledug Market.. To find out the product innovation carried out by Frozen Food Indah in Lembang Ciledug Market. A brief history of frozen food Indah Dipasar Lembang Ciledug Initially, the stall or frozen food business place Indah Dipasar Lembang Ciledug only provided frozen food or other ordinary frozen food in general. This frozen food place does not only eat frozen food but also various kinds of raw food such as tempeh and tofu and others. Over time, in 2023 after seeing the progress and smoothness of the frozen food and beverage business, it was very productive, as well as the great opportunities and potential, the idea arose from Indah Ernawati to open or frozen food Indah Dipasar Lembang Ciledug which is part of Pasar Lembang Cliedug Tangerang., Also adding new products like shops in general. Many choices of frozen food and the main product that is touted as the mascot of Indah frozen food in Lembang Ciledug Market is frozen food that is comfortable and quality for consumers to buy our products. Not only a choice of various types of frozen food products, Indah frozen food in Lembang Ciledug Market also provides various other types such as meatballs, tempeh, tofu, bean sprouts and many others. This makes more people or consumers interested in coming and buying more at the Indah frozen food place in Lembang Ciledug Market so that currently Indah frozen food in Lembang Ciledug Market always provides the latest and quality services and products.